Direct CP violation in charmless three-body decays of B± mesons - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; et al. (Physical review, 2023)
Measurements of CP asymmetries in charmless three-body decays of B± mesons are reported using proton-proton collision data collected by the LHCb detector, corresponding to an integrated luminosity of 5.9 fb−1. The previously observed CP asymmetry in B±→π±K+K− decays is confirmed, and CP asymmetries are observed with a significance of more than five standard deviations in the B±→π±π+π− and B±→K±K+K− decays, while the CP asymmetry of B±→K±π+π− decays is confirmed to be compatible with zero. The distributions of these asymmetries are also studied as a function of the three-body phase space and suggest contributions from rescattering and resonance interference processes. An indication of the presence of the decays B±→π±χc0(1P) in both B±→π±π+π− and B±→π±K+K− decays is observed, as is CP violation involving these amplitudes.
Im Text ist "+" und "-"hochgestellt
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 09.02.2024